2016
DOI: 10.1074/jbc.m115.712836
|View full text |Cite
|
Sign up to set email alerts
|

Expression of N-Acetylglucosaminyltransferase III Suppresses α2,3-Sialylation, and Its Distinctive Functions in Cell Migration Are Attributed to α2,6-Sialylation Levels

Abstract: N-Acetylglucosaminyltransferase III (GnT-III), which catalyzes the addition of the bisecting GlcNAc branch on N-glycans, is usually described as a metastasis suppressor. Overexpression of GnT-III inhibited migration in multiple types of tumor cells. However, these results seem controversial to the clinical observations for the increased expression of GnT-III in human hepatomas, glioma, and ovarian cancers. Here, we present evidence that these inconsistencies are mainly attributed to the different expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 63 publications
5
27
0
Order By: Relevance
“…S9A). This is consistent with previous reports showing that overexpression of GnT-III downregulates a2,3-sialylation but not a2,6-sialylation in cancer cell lines (64,65). Although this could be explained by the action of ST6GAL1 on O-glycans, the suppressive effects of GnT-III overexpression on SSA reactivity was not observed even in the presence of the O-glycosylation inhibitor, benzyl-GalNAc (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 93%
“…S9A). This is consistent with previous reports showing that overexpression of GnT-III downregulates a2,3-sialylation but not a2,6-sialylation in cancer cell lines (64,65). Although this could be explained by the action of ST6GAL1 on O-glycans, the suppressive effects of GnT-III overexpression on SSA reactivity was not observed even in the presence of the O-glycosylation inhibitor, benzyl-GalNAc (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 93%
“…We show that cellular populations with distinct α2,6-Sial levels coexist together within cell lines and may reflect linkage heterogeneity within tumor cell populations in vivo. The bimodal expression of α2,6-Sial shown here can also be evidenced in several reports for MDA_MB-231 as well as other cell lines but has not been investigated before (33)(34)(35)(36)(37). The α2,6-Sial heterogeneity is counterpoised with relatively homogeneous expression in the same cells for other glycans such as α2,3-Sial, fucose, T/Tn-antigen, bisecting/ biantennary complex N-glycans & tri/tetra antennary complex N-glycans.…”
Section: Discussionsupporting
confidence: 75%
“…Our MS glycan analysis revealed increases in various terminal epitopes of N-glycans in Mgat3-knockout brain, which is concomitant with complete loss of bisecting GlcNAc, suggesting that one of the physiological functions of bisecting GlcNAc is to suppress formation of mature and complex N-glycans [56]. Similarly, Dr. Gu's group reported that the level of bisecting GlcNAc is negatively correlated with the level of sialylation in various cell lines [61].…”
Section: Functional Overview Of Gnt-iiimentioning
confidence: 52%